A handbook on the Jewish roots of the Christian faith - Evans, Craig A. 1952-; Mishkin, David (Peabody, Massachusetts Hendrickson Publishers, 2019)
Part I. The soil -- 1. God's plan for Israel -- 2. God's plan for the nations -- 3. Messianic prophecies -- 4. Appointed times -- 5. Tabernacle and Temple -- Part II. The roots -- 6. The Jewish world of Jesus -- 7. The Jewish life and identity of Jesus -- 8. The Jewish teachings of Jesus -- Part III. The trunk -- 9. The Jewish disciples -- 10. The Jewish Paul -- 11. The Jewish message: resurrection -- Part IV. The branches -- 12. The parting ways -- 13. The mending of the ways.
Part I. The soil. --The kingdom and the covenants /Noaam Hendren --The Abrahamic covenant /The Mosaic covenant /Kevin Chen --The Davidic covenant /Brian J. Kinzel --The New covenant /Noam Hendren --The nations in the Torah /Yohanan Stanfield --The nations in the Prophets /Brian J. Kinzel --The nations in the writings /Kevin Chen --The messiah in the Torah /Seth D. Postell --The messiah in the Prophets /Michael L. Brown --The messiah in the writings /Brian J. Kinzel --New Testament use of the Old Testament /Craig A. Evans --The sabbath /Eitan Bar --Passover, unleavened bread, firstfruits /Erez Soref --Shavuot /Golan Brosh --The fall feasts /Noam Hendren --Purim /Golan Brosh --Hanukkah /Eitan Bar --Atonement in the Old Testament /Michael L. Brown --Salvation in the Old Testament /Michael L. Brown --Jesus and the Tabernacle/Temple /George H. Guthrie.
Part II. The roots. --The Jewish land and archaeology of Jesus /Sheila Gyllenberg --Jewish groups in the first century /Jim R. Sibley --Jewish literature of the Second Temple Period /Sheila Gyllenberg --The Jewish institutions /Andreas Stutz --Messianic expectations /Andreas Stutz --The life and ministry of Jesus /Craig A. Evans --Son of man : Daniel 7 /Andreas Stutz --I am statements /Andreas J. Köstenberger --Early Jesus-devotion /Larry W. Hurtado --Jesus as rabbi /Andreas J. Köstenberger --The Lord's Prayer /Scot McKnight --The Sermon on the Mount /Scot McKnight --Parables of Jesus /Russell Morton.
Part III. --The Jewish disciples in the Gospels /Andreas J. Köstenberger --The Jewish disciples in the Book of Acts /Jim R. Sibley --The Jewishness of the Book of Hebrews /George H. Guthrie --Jews and Judaism in the Gospel of John /Craig A. Evans --Paul's life /Jason Maston --Paul in modern scholarship /Brian S. Rosner --Paul's view of the law /Brian S. Rosner --Paul's view of Israel and the nations /Jim R. Sibley --Resurrection in the Old Testament /Kevin Chen --Resurrection in the Second Temple Period /Jason Maston --Resurrection in Paul's theology /Paul T. Sloan --Jewish perspectives on the resurrection of Jesus /David Mishkin.
Part IV. --Early Judaism /Dacid Mishkin --Early Christianity /Jason Maston --The Middle Ages /Ray Pritz --Jewish believers in Jesus in modern Israel /Erez Soref --Jewish and Arab believers in Jesus in modern Israel /Erz Soref,Thomas Damianos.
Hier auch später erschienene, unveränderte Nachdrucke
Includes bibliographical references and index
Archivierung/Langzeitarchivierung gewährleistet
Keywords: Bible -- Criticism, interpretation, etc; Christianity -- Origin; Church History -- Primitive and early church, ca. 30-600; Judaism -- Relations -- Christianity; Christianity and other religions -- Judaism; Bible; Christianity; Christianity ; Origin; Church history ; Primitive and early church; Interfaith Relations; Judaism; Criticism, interpretation, etc